2014
DOI: 10.3329/bjp.v9i3.19026
|View full text |Cite
|
Sign up to set email alerts
|

A diterpenoid sugiol from <i>Metasequoia glyptostroboides</i> with α-glucosidase and tyrosinase inhibitory potential

Abstract: Nowadays use of plant derived natural compounds have become a topic of increasing interest in food and medicine industries due to their multitude of biological and therapeutic properties. In this study, a diterpenoid compound sugiol, isolated from Metasequoia glyptostroboides was evaluated for α-glucosidase and tyrosinase inhibitory efficacy in terms of its potent antidiabetic and anti-melanogenesis potential, respectively. As a result, sugiol at the concentration range of (100-10,000 µg/mL) and (20-500 µg/mL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Bajpai and Kang [ 57 ] evaluated sugiol for tyrosinase and α-glucosidase inhibitory activity in vitro, in terms of its antimelanogenesis and antidiabetic potential, respectively. The results showed that sugiol at the concentration range of 0.100 to 10 mg/mL presented efficacy on inhibiting α-glucosidase (12.34 to 63.47% of inhibition) similar to acarbose (19.2 to 65.5% of inhibition at same concentration range), while at concentration 0.020 to 0.50 mg/mL, sugiol inhibits 28.2 to 67.4% of tyrosinase activity, only a little less active than kojic acid used as reference (32.4 to 76.5% inhibition at the same concentration range).…”
Section: Bioactive Secondary Metabolites From Juniperus mentioning
confidence: 99%
“…Bajpai and Kang [ 57 ] evaluated sugiol for tyrosinase and α-glucosidase inhibitory activity in vitro, in terms of its antimelanogenesis and antidiabetic potential, respectively. The results showed that sugiol at the concentration range of 0.100 to 10 mg/mL presented efficacy on inhibiting α-glucosidase (12.34 to 63.47% of inhibition) similar to acarbose (19.2 to 65.5% of inhibition at same concentration range), while at concentration 0.020 to 0.50 mg/mL, sugiol inhibits 28.2 to 67.4% of tyrosinase activity, only a little less active than kojic acid used as reference (32.4 to 76.5% inhibition at the same concentration range).…”
Section: Bioactive Secondary Metabolites From Juniperus mentioning
confidence: 99%
“…Interestingly, gomisin is a lignin compound that can be isolated from plants of the Schisandraceae family [ 32 ]. It is also known to have anti-diabetic activity by increasing AMPK phosphorylation [ 33 ], anti-oxidant, anti-tumor, and anti-inflammatory [ 34 ]. On the other hand, Fig 1 also shows that the presence of sugiol was indicated by the proton signals at chemical shifts of 0.59 (s), 0.83 (m, 6H), 0.97 (m, 1H), 1.20 (m, 5H), 1.41 (s) 1.60 (s), 1.81 (s), 1.93 (s), 2.46 (p, J = 1.8 Hz, 2H), 2.58 (s), 6.88 (s), 7.5 (s, OH), 7.75 (s).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Fig 1 also shows that the presence of sugiol was indicated by the proton signals at chemical shifts of 0.59 (s), 0.83 (m, 6H), 0.97 (m, 1H), 1.20 (m, 5H), 1.41 (s) 1.60 (s), 1.81 (s), 1.93 (s), 2.46 (p, J = 1.8 Hz, 2H), 2.58 (s), 6.88 (s), 7.5 (s, OH), 7.75 (s). Sugiol is a diterpenoid compound that can be isolated from Metasequoia glyptostroboides and the compound exhibited a large number of inhibitory effects on the α-glucosidase and tyrosinase enzymes tested in vitro [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that about 40% of the tested bioactive substances present problems related to low water solubility (Savjani et al, 2012), including natural products (Coimbra et al, 2011). This is the case of sugiol, a diterpenoid isolated from the bark of several trees from the Cupressaceae family, such as Cupressus sempervirens (Zhang et al, 2012) , Cupressus geovania (Jolad et al, 2005) , Cupressus lusitanica (Mohareb et al, 2010) , Calocedrus formosana (Chao et al, 2005) , Metasequoia glyptostroboides (Bajpai and Kang, 2014), and Pilgerodendron uviferum (Solís et al, 2004). Despite unsatisfactory water solubility previously reported (Sengupta et al, 1960), sugiol has already been shown to have anti-inflammatory, antibacterial, and anti-cancer properties during in vitro assays (Bajpai and Kang, 2011; Sengupta et al, 2011; Jung et al, 2015; D'yakonov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%